An assessment of the quality of primary health care in India - Powell-Jackson, T; Acharya, A; Mills, A (2013)
There is limited evidence on the quality of primary health care provision in India. Using data on the availability of inputs from a nationally representative survey of primary health centres, a composite measure of structural quality of care for primary health centres was developed with a view to examine its geographical variation, associations with mortality and healthcare utilisation, and the determinants of better quality, giving particular attention to the role of management. The mean quality score was 52%, with large differences across regions, states and districts. Quality of care was the worst and the variation greatest in states designated by the government as low performing. Good management practices in a facility were highly correlated with better quality of care. The majority of primary health facilities in India fall far short of government minimum standards, in part explaining why most people in rural areas use private providers for outpatient care. Future research should explore the causal relationship between management practices, quality of care and patient outcomes.